Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.21157/j.ked.hewan.v12i4.10215
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF MALACCA LEAVES (Phyllantus emblica) ETHANOLIC EXTRACT ON Plasmodium falciparum GROWTH IN VITRO

Abstract: The aim of this research was to find out in vitro antiplasmodium activity of Malacca leaves (Phyllantus emblica) ethanolic extract against Plasmodium falciparum growth. In this study, Plasmodium culture contained 5% parasitemia in ring stage was cultured using candle jar method and antiplasmodial activity test was carried out using microculture. The treatments were divided into 7 groups with four repetitions. K1 as negative control group was given Roswell Park Memorial Institute (RPMI), while K2 as positive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Among such plants is the Malacca plant that has been reported to have antiparasitic and immune-enhancing properties and is also used for medicinal purposes and as a source of vitamins [ 8 ]. A previous study has demonstrated that the ethanolic extract of Malacca leaves inhibited the growth of P. falciparum at a concentration of 100 μg/ml, with an ability to inhibit 50% growth of P. falciparum at 3889 μg/ml [ 9 ]. The fruits, leaves, and roots of the Malacca tree contain polyphenols (tannins) and flavonoids [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among such plants is the Malacca plant that has been reported to have antiparasitic and immune-enhancing properties and is also used for medicinal purposes and as a source of vitamins [ 8 ]. A previous study has demonstrated that the ethanolic extract of Malacca leaves inhibited the growth of P. falciparum at a concentration of 100 μg/ml, with an ability to inhibit 50% growth of P. falciparum at 3889 μg/ml [ 9 ]. The fruits, leaves, and roots of the Malacca tree contain polyphenols (tannins) and flavonoids [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ekstrak daun malaka juga efektif digunakan untuk pengobatan kemoterapi (Singh et al, 2011), antivirus, antimutagenik, antialergi (Khopde et al, 2001 dan antimalaria (Asmilia et al, 2018) antitumor (Sumalatha, 2013), antimikroba, antibakteri, antijamur (Singh et al, 2015). Hingga saat ini belum ada penelitian daun malaka sebagai pengobatan alternatif untuk penyakit tripanosomiasis.…”
Section: Pendahuluanunclassified
“…Numerous studies have been done on the Malacca plant which reported that the Malacca plant has a potency as chemoprotective and antioxidant [6], analgesic, antipyretic [12], antitumor [13,14], anti-inflammation [15,16], able to decrease blood sugar level [17], antiviral, antimutagenic, and antiallergic [18], antimicrobial, and antibacterial antifungals [19,20]. Malar and Mary [21] proved that the fruit of Malacca can appear to be able to repair liver damage, and Asmilia et al [22] reported that the ethanolic extract of Malacca leaves has a higher inhibition level on Plasmodium falciparum growth compared to ethyl acetate and n-hexane extract of Malacca leaves. Deepak and Gopal [23] found terpenes, phytosterols, and terpenoids in ethyl acetate extracts from the bark of Phyllanthus emblica.…”
Section: Introductionmentioning
confidence: 99%